Meta-analysis comparing growth performance, carcass characteristics, and water usage of growing-finishing pigs fed using conventional dry and wet-dry feeders - Nitikanchana, S.; Tokach, Michael D.; DeRouchey, Joel M.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Fifteen trials were used for meta-analyses comparing the effects of conventional dry (CD) and wet-dry (WD) feeders on growth performance, carcass traits, and water usage of growing-finishing pigs. The meta-analysis indicated that pigs fed with WD feeders consistently had greater (P < 0.01) ADG (0.09 lb/d) and ADFI compared with those fed with CD feeders; however, although highly variable, no overall difference (P = 0.93) was observed in F/G. As a result of improved growth rate, final BW and HCW of pigs fed with WD feeders was 3.2% greater (P < 0.01) than when fed with CD feeders. For carcass traits, backfat was greater (P < 0.01) and percentage lean was lower (P < 0.01) in pigs fed with WD feeders compared with those fed with CD feeders. Carcass yield and loin depth did not differ (P > 0.14) among feeder types. Water usage for pigs fed with WD feeders was 0.4 gal/pig/d less (P = 0.02) than for pigs using CD feeders. Growing-finishing pigs fed with WD feeders had increased growth rate, feed intake, final BW, and HCW, but deposited more fat as indicated by greater backfat and lower percentage lean.
Keywords: Swine; Conventional dry feeder; Wet-dry feeder; Finishing pig; Meta-analysis